In-Stent Stenosis After Pipeline Embolization Device in Intracranial Aneurysms: Incidence, Predictors, and Clinical Outcomes. Issue 6 (21st December 2022) - Turhon, Mirzat; Kang, Huibin; Liu, Jian; Zhang, Yisen; Zhang, Ying; Huang, Jiliang; Wang, Kun; Li, Mengxing; Liu, Jianmin; Zhang, Hongqi; Li, Tianxiao; Song, Donglei; et al.
Abstract : BACKGROUND: In-stent stenosis (ISS) is a delayed complication that can occur after pipeline embolization device use when treating intracranial aneurysms (IAs). OBJECTIVE: To assess the incidence, predictors, and outcomes of ISS. METHODS: This was a retrospective, multicenter, observational study. All patient data were collected from a PLUS registry study. We collected data from patients with IA who completed digital subtraction angiography at follow-up and divided patients into "non-ISS, " "mild ISS, " or "severe ISS" groups. Multivariate logistic regression analysis was conducted to determine predictors of ISS. RESULTS: A total of 1171 consecutive patients with 1322 IAs participated in this study. Angiographic follow-up was available for 662 patients with 728 IAs, and the mean follow-up time was 9 months. ISS was detected in 73 cases (10.03%), including 61 mild ISS cases and 12 severe ISS cases. Univariate and multivariable analysis demonstrated that current smoking history (mild ISS: OR 2.15, 95% CI 1.122-4.118, P = .021; severe ISS: OR 5.858, 95% CI 1.186-28.93, P = .030) and cerebral atherosclerosis (mild ISS: OR 5.694, 95% CI 3.193-10.15, P = .001; severe ISS: OR 6.103, 95% CI 1.384-26.91, P = .017) were independent predictors of ISS. Compared with the other groups, the severe ISS group had higher rate of ischemic stroke (33.3%). CONCLUSION: ISS occurs in approximately 10.03% of cases at a mean follow-up of 9 months. Statistically, current smoking history and cerebral atherosclerosis are the main predictors of ISS. Severe ISS may be associated with higher risk of neurological ischemic events in patients with IA after pipeline embolization device implantation.